2014
DOI: 10.2478/eces-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phytotoxicity of Selected Phosphonium Ionic Liquid

Abstract: Ionic liquids have attracted considerable interest in various areas as new, non-volatile and nonflammable organic solvents, catalysts, reaction additives, ligands, drugs and other dedicated materials etc. Their general use, sometimes in bulky quantities, requires determination of their potential ecotoxicity on selected organisms. In the present work, influence of triphenylmethylphosphonium iodide (1) and triphenylhexadecylphosphonium iodide (2), introduced to soil, on germination and early stages of growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
(99 reference statements)
1
10
0
Order By: Relevance
“…The results of the research have shown that the toxic effect of chemical substances on terrestrial plants depends on their concentration. Similar opinion has been presented in the literature for different group of the ionic liquids [23]. Another factor conditioning the toxicity of chemical substances are of plant species and varieties [4,24,25], which was also confirmed in this work.…”
Section: Resultssupporting
confidence: 91%
“…The results of the research have shown that the toxic effect of chemical substances on terrestrial plants depends on their concentration. Similar opinion has been presented in the literature for different group of the ionic liquids [23]. Another factor conditioning the toxicity of chemical substances are of plant species and varieties [4,24,25], which was also confirmed in this work.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the smaller and lighter the anions are the more biocompatible the AAILs are. However, according to some authors the anions of IL do not affect the ecotoxicity but instead determines their physical and chemical properties which include solubility, viscosity and melting temperatures [54,55]. Recent studies indicate that the anion effect has been overlooked for it possibility to contribute to the overall toxicity [44]; focusing on fluorine as the anion which collectively played role in the toxicity of the ILs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the phosphonium derivatives triphenylphosphonium iodide and triphenylhexadecylphosphonium iodide exhibit high toxicity towards spring barley Hordeum vulgare and common radish Raphanus sativus . In fact, just 80 mg of triphenylphosphonium iodide and 100 mg of triphenylhexadecylphosphonium iodide per 1 kg of dry soil mass for both the spring barley and common radish can cause detectable effects on the growth and germination of plants . Imidazolium‐based ILs also exhibit potential phytotoxicity to these species, but to a lesser extent.…”
Section: Toxicological Impact Of Ionic Liquidsmentioning
confidence: 99%